End Users’ Acceptance of Clinical Information - van Zyl, Jacobus Gert (My University, 2011)
Health care organisations around the world are under increasing pressure to improve the quality of care they provide without increasing cost. The use of information technology in health care offers an opportunity to address this issue, but unsuccessful implementations of information technology into this environment limit the potential benefits. The purpose of this research is to investigate the factors that influence end user acceptance of information technology in the health care environment by means of a case study. The main findings of the research were that information technology acceptance by end users in the health care environment is influenced not only by factors relating to the technology, but also by social and cultural factors. By paying attention to these non-technological issues and by focusing resources on problem areas prior to implementation, the likelihood of a successful information technology implementation into the health care environment might be increased
MBA - WBS
Keywords: Health care organisations; Hospitals